Determinants of Technology Adoption and Financial Ratios on Banking Performance in Indonesia Through Net Interest Margin as Mediation - Endah Suci Damayanti; Adler Haymans Manurung; Yayan Hendayana; Wastam Wahyu Hidayat (Universitas Bangka Belitung, 2025)
The purpose of this study is to explore the relationship between technology adoption, financial ratios that can affect banking performance in Indonesia through the mediation of Net Interest Margin. The research approach is Explanatory Research with purposive sampling technique obtained 35 go pubic banks selected with 9 years of financial statement data from 2015 to 2023 so as to obtain 315 observations. The research findings show that BOPO strongly influences the NIM variable, giving rise to direct and indirect effects. All direct effects are the largest affecting ROA. Company management must manage Technology Adoption, NPL, LDR, Quality of Earning Assets (QEA) and BOPO to influence Banking Performance. Company management must manage these ratios to provide high ROA so that investors are interested in buying banking stocks. The efficiency of the company represented by BOPO needs to be managed so that NIM increases and can be limited to the maximum.